Oil city of Abadan (1908-1951): history, valorisation and patrimonialisation - Khazaee, Mohammad (2021)
Abstract: Oil City of Abadan (1908-1951) Buildings, structures, and landscapes associated with the activities of an industry in a city are like a birth certificate representing the history and identity of a city. Over time, some of these structures are damaged or lost, thus protecting, restoring and transferring these architectural spaces into new urban activity can be used to preserve the identity and history of the city for the future generation and contribute to sustainable development. This thesis studies the history of oil industry in Iran and the oil refinery in the city of Abadan between 1908 when the first well reached to the oil in the City of Masjid-i Suleiman until 1951 which was the time of nationalization of Iran oil industry, it concerns a practice of company town, and especially the history of oil industry and also development of Abadan city, its architecture, urban design, landscape and a viewpoint over industrial heritage and related museums. Therefore, the main approach in this research is the interpretation, valorization, and representation of the industrial heritage related to the oil industry. For this purpose, this study carries out with the consideration of Abadan city located in the southwest of Iran as a case study. The first chapter of this thesis includes a brief history of the oil industry in Iran and the APOC oil company. The second chapter covers the formation and development of Abadan city around an oil refinery and the architectural and urbanization aspects and a view on the social aspects and the structure of the community. Chapter 3 discuss heritage and present industrial heritage practices in Iran such as oil industry museums. The expected results of this research could be identifying and interpreting the associated values with the industrial and cultural heritage in the city and contribute protection of this urban complex. These results can be used to retain the city's identity and to conserve the values and status of the past society, they could be used by government officials and active groups concerning the heritage. Also by producing scientific papers other researchers in this field could take benefit from these results as well as they could be used for raising awareness of local community about the their heritage.